The Pelatihan Peningkatan Keterampilan Pemantauan Tumbuh Kembang Anak oleh Kader Posyandu pada Wilayah Kerja Puskesmas Motui Konawe Utara - Imanuddin, Imanuddin; Kusumawati, Evi; Astati; Rosnah; Hariani; Kasmawati; Sudarsono, I Made Rai (Jurnal Inovasi, Pemberdayaan dan Pengabdian Masyarakat, 2025)
Posyandu cadres have a strategic role in monitoring child growth and development, but their limited skills can hinder service optimization. This community service activity aims to improve the skills of posyandu cadres through practice-based training in the Motui Health Center work area, North Konawe. Training methods include lectures, simulations, group discussions, and field practice. The results showed an increase in cadre skills in monitoring child growth and development (from 50.0% to 73.3%), measuring body dimensions (from 90.0% to 100%), and counseling (from 66.7% to 90.0%). The average cadre skill score also increased, especially in measuring body dimensions with an increase of 21.6 points. This training shows that cadre training helps improve child growth and development monitoring skills. It is recommended that ongoing training programs and routine refresher courses be provided evenly to ensure optimal quality of posyandu services.